Manajemen Pengelolaan Buku di Micro-Library Sembulang, Batam, Kepulauan Riau - Nurlaily Nurlaily; Mochamad Nuruz Zaman (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2020)
In the current era, many of our people do not know much about the importance of reading. Especially for ordinary people who have never read or written at all. Their insight may still be influenced by verbal, not written. This is both caused by there may be a lack of reading books and they don't have a large collection of books. The library in Sembulang village is in the form of a micro-library that can help the community to get to know writing and enjoy reading. The library is a special alternative for rural communities whose communities are still innocent or have not been intervened by city people. Later, the village community will be introduced to what is a micro-library, its functions, and so on. The other benefits of the micro-library in Sembulang are able to improve children's learning quality, introduce the importance of reading to the community, and increase the source of income for local villages. Of all these, it will first be explained to all local village people how to borrow or read in the library. The method used will be made socialization about the introduction of the library and its functions.